Analysis of Reasoning Ability and Mathematical Communication Based on Learning Styles on PMRI Learning (Journal of Primary Education, 2018)
This study aims to determine the mastery of reasoning ability and mathematical communication, the difference of reasoning ability and mathematical communication in the two sample classes, and also describes the students' reasoning and communication ability. Type of research used is mix method. Quantitative research with random sampling technique while qualitative research with purposive technique. Data collection uses observation, tests, questionnaires, and interviews. The learning mastery test shows that the reasoning ability and the mathematical communication of the experimental class learners reaches completeness. The average difference test shows that the reasoning ability and the experimental mathematics of the experimental class is better than the control class. Based on the learning style not all students who have good reasoning ability, the communication skills are good, and vice versa. This research is expected to be useful to be a source of information in answering the problems that occur in the learning process, especially in improving student learning outcomes in sub rectangular themes.